Analysis of Marketing Communication Strategy for the Tourism Office of West Nusa Tenggara Province through the Official Instagram Account @Lomboksumbawa.Go - Adinda Dewi Shalsabilla; Kharisma Nasionalita (Budapest International Research and Critics University, 2022)
Tourist visits to the Province of West Nusa Tenggara at the end of 2021 will undoubtedly be an excellent opportunity for progress in improving the economy both regionally and nationally. However, along with the COVID-19 pandemic, visits are often blocked. Therefore, it is necessary to maximize the use of social media for digital promotion. This research uses qualitative methods with a case study approach to marketing communication strategies. This study aimed to determine the marketing communication strategy of the West Nusa Tenggara Provincial Tourism Office through the official Instagram account @lomboksumbawa.go. The study's results indicate that the marketing communication strategy on Instagram @lomboksumbawa.go can be seen through the concept of an effective marketing communication strategy developed by Machfoedz (2010). In the message strategy, the elements of communication information include information on accommodation, tourist destinations, creative economy, events, activities, and policies from the NTB Provincial Tourism Office and the Government, as well as public information. In creative form, message elements with rational messages and emotional messages are packaged in the form of photos, videos, and texts. In the media strategy, the media selection element of the West Nusa Tenggara Province Tourism Office focuses on Instagram as the primary medium of marketing communication. The second element is related to the consumer gap. The West Nusa Tenggara Provincial Tourism Office chooses the target audience and the right time to determine the upload of content or messages on Instagram.